Obesity and chronic diseases prevention among school children: nursing intervention in healthy eating education: Obesity and chronic diseases prevention - Vitale, Elsa; Fortunato, Rosa Silvia; Della Pietà, Cosimo; Ciurlia, Maria Luisa; Germini, Francesco (Progress in Nutrition, 2021)
Objective: The aim of this research was to explore the food frequency assumption among a sample of school children by assessing nursing interventions in eating education. Design: A correlation study was performed to assess the effectiveness of nursing education in healthy eating among schoolchildren. Setting: Anthropometric parameters were recorded and a Food Frequency Questionnaire was performed by participants and their parents at the enrollment moment (T0) and after six months (T1) from the nursing educational reunion. Participants: 33 schoolchildren who attended the elementary school were enrolled after their parents gave their consents to participation. Results: Differences between BMI were not significant as well as we consider the sex subgroups. Conclusion: Child care contexts provide a salient chance to control children’s eating habits in preschool and school age thanks to knowledge of healthy eating lifestyles.